Quo Vadis Polemik Jaminan Hari Tua (JHT) Bagi Masa Depan Tenaga Kerja di Indonesia dalam Peraturan Menteri Ketenagakerjaan Nomor 2 Tahun 2022 - Mila Amalia Fitri; Farina Firda Eprilia; Fajry Awwaliyah Praptiwi (Jurnal Hukum Lex Generalis, 2022)
The government of Indonesia released the Minister of Manpower Regulation Number 2 of 2022 concerning Old Age Security as social protection to ensure the life of workers in retirement, but this regulation lead to polemics in various circles. This study uses a normative juridical method with reference to secondary legal materials in the form of legislation and library materials. The results of the study indicate that the reason for the existence of this Law is because it is considered not included in the sociological requirements and the General Principles of Good Governance as attached in the Government Administration regulation. The government should be able to put forward the needs of the civil country so that it does not only fulfill the interests of a few people.